PHYTOCHEMISTRY AND ETHNOPHARMACOLOGY OF THE SEA GRASS CYMODOCEACEA FAMILYâ€“ A REVIEW - N, Pushpa Bharathi; V, Vanitha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Cymodoceaceae is a family of flowering plants, sometimes known as the manatee-grass family,â€ the family Cymodoceaceae includes only marine species. The angiosperm phylogeny II system, of 2003 (unchanged from the APG system, of 1998), does recognize Cymodoceaceae and places it in the order Alismatales, in the clade monocots. They are marine hydrophytes that grow and complete their life cycle in a submerged condition, in a saline environment. Like terrestrial plant they obtain their energy from light through photosynthesis thus, they grow only in clear and shallow water, and at the suitable condition, they form beds or meadows. The family includes five genera, totalling 16 species of marine plants occurring in tropical seas and oceans (so-called seagrasses). Cymodoceaceae consist of five genera such as Amphibolis, Cymodocea, Halodule, Syringodium, and Thalassodendron. In this genera Cymodocea rotundata Ehrenb. and Hempr. Ex Asch. Cymodocea serrulata, (R.Br.) Asch. and Magnus, Halodule pinifolia (Miki) Hartog, Halodule uninervis (Forssk.) Asch and Syringodium isoetifolium (Asch.) are the species mostly adopted in Indian coastal region. These seagrass species have unique nature and wide application to the environment including human being. In this article botanical aspects, phytochemistry and ethnopharmacology of these five seagrass species belong to Cymodoceaceae family will be discussed.